Answers

2016-01-26T21:19:55+05:30
Let us consider ABC as a right angled triangle with AB as hypotenuse,AC as height and BC as base.
It is given in the question that AC=BC and AB^2=2AC^2
Now ,in a right angled triangle ,
hypotenuse^2=base^2 +altitude^2
So according to the theorem in this case,
AB^2=AC^2+BC^2
In the question it is clearly mentioned that AC=BC
ie;AB^2=AC^2+AC^2
ie;AB^2=2AC^2
Hence proved
0
2016-01-26T21:20:21+05:30
As ac = bc
so ac^2+bc^2 = ac^2+ac^2 = 2(ac)^2
acc to pythagorous thm
ab^2= ac^2 + bc^2 = 2(ac)^2 
so ab^2= 2ac^2
hence verified
0